THE JUNIOR LEARNER’S MORAL – ETHICAL EVALUATION ACTION BUILDUP - Vitkovskaya, Irina; Khrabrova, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The moral – ethical evaluation action in the federal state educational standard of primary education is regarded as a universal educational activity, the formation of which provides the optimal development of junior learners, the possibility of a successful continuation of education, adaptation in society.The article describes one of the approaches to the formation of the action based on the content of the subject "Fundamentals of Orthodox Culture"